In vitro and in silico assessment of antitumor properties and biomolecular binding studies for two new complexes based on NiII bearing k2N,S-donor ligands - Farias, R. L. [UNESP]; Polez, A. M.R. [UNESP]; Silva, D. E.S. [UNESP]; Zanetti, R. D. [UNESP]; Moreira, M. B. [UNESP]; Batista, V. S. [UNESP]; Reis, B. L. [UNESP]; Nascimento-Júnior, N. M. [UNESP]; Rocha, F. V.; Lima, M. A.; Oliveira, A. B.; Ellena, J.; et al. (Elsevier, 2021)
This work deals with two new molecule-based materials, namely NiII-complexes of general formulae [Ni(L1)2] (Ni1) and [Ni(L2)2] (Ni2), where L1 = trans-cinnamaldehyde-N(4)-methyl thiosemicarbazone and L2 = trans-cinnamaldehyde-N(4)-ethyl thiosemicarbazone, as potential antitumor agents. Both compounds were characterized by elemental analysis, molar conductivity and spectroscopic techniques (FTIR and NMR). Their molecular structures were obtained by single-crystal X-ray diffraction analysis. Each one crystallizes in a monoclinic space group P 21/c, also the asymmetric unit comprises of one NiII ion located on an inversion centre and one anionic ligand, which acts as a κ2N,S-donor affording a five-membered metallaring. The compounds were screened against two selected tumour cell lines (MCF-7 and A549) and non-tumour fibroblasts cell line (MRC-5) via MTT assays. In both tumour cells, all compounds exhibited higher cytotoxicity than the control drug (cisplatin). The IC50 values ranges of 3.70 – 41.37 μM and 1.06 – 14.91 μM were found for MCF-7 and A549, respectively. Importantly, all of them were less toxicity than cisplatin in MRC-5 with SI values ranged at 11.80 – 86.60. The red blood cell (RBC) assay revealed Ni2 as non-toxic due to its reduced haemolytic effect (0‐–9% at 1‐–10 μM). The DNA binding was investigated through a combination of spectrophotometric absorption and emission titrations, electrophoresis, and circular dichroism experiments. As a result, these metal complexes were not able to strongly binding to DNA (Kb values ~104 mol L‐−1) but suggesting groove-binding interactions. The scavenging ability of them towards 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical was also evaluated in this work, but no important antioxidant behaviour was detected. Further, the interaction of Ni1 and Ni2 to human serum albumin (HSA) was explored by quenching of tryptophan emission, warfarin competitive assay, and molecular docking protocols. The HSA binding analyses indicated good affinity of both complexes to Sudlow site I (Kb values ⁓103 mol L−1).
Keywords: Metallodrugs; mMolecular docking; N,S-donor ligands; Nickel(II)-complexes; Protein-ligand binding studies